Perbandingan Pemberiaan Tablet Fe + Asam Folat dan Tablet Fe + Vitamin C Terhadap Peningkatan Kadar Hemoglobin - Azrida Machmud; Halida Thamrin (FORIKES, 2019)
For children and adolesence, there are many health problems, especially anemia. Anemia is one of the common nutritional problems in the world, especially in developing countries. The purpose of this study was to determine the comparison of administration of Fe tablets + folic acid and Fe tablets + vitamin C to increasing Hb levels in midwifery students at the Muslim University of Indonesia. This type of research was a quasi experimental study with the pre test post test design. The sample was taken by purposive sampling technique with sample size of 32 female students.The results of this study there was a difference in the increase in hemoglobin levels in the group supplementing Fe + Folic Acid and Fe + Vitamin C. The statistical test results using the T-test obtained a mean difference of 0.47, p = 0.036. Giving Fe + folic acid tablets is more effective to increase hemoglobin levels Keywords: adolesence; Hb; Fe; folic acid; vitamin C